Complement activation in infective endocarditis: correlation with extracardiac manifestations and prognosis - Messias-Reason, Iara; Hayashi, S Y; Nisihara, R M; Kirschfink, Michael (Clinical & experimental immunology, 2002)
In an infectious process complement activation is necessary for a proper immune and inflammatory response, but when exacerbated may cause tissue injuries. In infective endocarditis (IE) patients tend to develop high titres of circulating immune complexes (CIC) that activate complement. The aim of this study was to evaluate for the first time complement activation in IE for possible correlation with extracardiac manifestations and clinical prognosis. Twenty patients with IE, 14 healthy controls and 15 patients presenting mitral and aortic valve lesions (with no signs of either infection or other associated diseases), were studied. Plasma levels of C3adesArg, SC5b-9, C1rs-C1Inh and C3b(Bb)P were determined by ELISA and C3d by double decker immunoelectrophoresis. C3 and C4 levels were assayed by turbidimetry and CIC by ELISA. Elevation of plasma levels of all complement activation products, with the exception of C3b(Bb)P, indicated a significant classical pathway activation in IE patients when compared to controls (C3d: P < 0·00004; C3adesArg: P < 0·03, SC5b-9: P < 0·01, C1rs-C1Inh: P < 0·00007). CIC levels were significantly increased (P < 0·005) and C3 reduced in IE patients (P < 0·05). Elevated C3d (P < 0·02) and C3adesArg (P < 0·03) levels were associated with pulmonary manifestations. In addition, C3d was significantly elevated in the patients who died when compared to those who had a good recovery (P < 0·02). Our data demonstrate the activation of the complement classical pathway, most probably mediated by CIC, in IE and suggests C3d and C3adesArg as possible markers for extracardiac lesion and severity of the disease.